Synthesis, physical and chemical properties, antihypoxic activity of some 5-[((5-(adamantane-1-yl)-4-R-4H-1,2,4-triazole-3-yl)thio)methyl]-N-R1-1,3,4-thiadiazole-2-amines and 5-[((5-(adamantane-1-yl)-4-R-4H-1,2,4-triazole-3-yl)thio)methyl]-4-R1-4H-1,2,4-t - V. M. Odyntsova; Ye. G. Knysh; O. I. Panasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Today, an increase of natural and technogenic situations leads to the disorders of the central nervous system, functional-metabolic processes, vascular diseases, in particular, acute cerebral blood flow disorders. In addition, the changes occurring on the molecular and cellular levels are in the basis of the functional violations of individual systems and the organism as a whole. Hypoxia not only complicates the disease course, but in most cases, determines its outcome. The important role in the fight against hypoxia belongs to antioxidants, which improve the circulating oxygen utilization by the body, reduce its need for the organs and tissues, which is not only expedient but necessary for the treatment of many acute and chronic pathological processes. So, the frequency of the hypoxic states and a wide range of factors causing them determine the relevance of new ways and methods finding to overcome the oxygen deficiency.